CD26 expression is attenuated by TGF‐β and SDF‐1 autocrine signaling on stromal myofibroblasts in human breast cancers. (29th May 2019) - Mezawa, Yoshihiro; Daigo, Yataro; Takano, Atsushi; Miyagi, Yohei; Yokose, Tomoyuki; Yamashita, Toshinari; Morimoto, Chikao; Hino, Okio; Orimo, Akira
Abstract: Human breast carcinoma‐associated fibroblasts (CAFs) increasingly acquire both transforming growth factor‐β (TGF‐β) and stromal cell‐derived factor‐1 (SDF‐1) signaling in an autocrine fashion during tumor progression. Such signaling mediates activated myofibroblastic and tumor‐promoting properties in these fibroblasts. CD26/dipeptidyl peptidase‐4 is a serine protease that cleaves various chemokines including SDF‐1. Stromal CD26 expression is reportedly undetectable in human skin squamous cell carcinomas. However, whether stromal CD26 expression is also downregulated in human breast cancers and which stromal cells potentially lack CD26 expression remain elusive. To answer these questions, sections prepared from 239 human breast carcinomas were stained with antibodies against CD26 and α‐smooth muscle actin (α‐SMA), a marker for activated myofibroblasts. We found that tumor‐associated stroma involving α‐SMA‐positive myofibroblasts stained negative or negligible for CD26 in 118 out of 193 (61.1%) tumors, whereas noncancerous stromal regions of the breast showed considerable staining for CD26. This decreased stromal CD26 staining in tumors also tends to be associated with poor outcomes for breast cancer patients. Moreover, we demonstrated that CD26 staining is attenuated on stromal myofibroblasts in human breast cancers. Consistently, CD26 expression is significantly downregulated in cultured CAF myofibroblasts extracted from human breast carcinomas as compared to control human mammary fibroblasts. Inhibition of TGF‐β or SDF‐1 signaling in CAFs by shRNA clearly upregulated the CD26 expression. Taken together, these findings indicate that CD26 expression is attenuated by TGF‐β‐ and SDF‐1‐autocrine signaling on stromal myofibroblasts in human mammary carcinomas, and that decreased stromal CD26 expression has potential as a prognostic marker. Abstract : Human breast carcinoma‐associated fibroblasts (CAFs) increasingly acquire both transforming growth factor‐β (TGF‐β) and stromal cell‐derived factor‐1 (SDF‐1) signaling in an autocrine fashion during tumor progression. We found that CD26 expression is attenuated by TGF‐β‐ and SDF‐1‐autocrine signaling on stromal myofibroblasts in human mammary carcinomas, and that decreased stromal CD26 expression has potential as a potential prognostic marker.